A review of catalytic hydrogenation of carbon dioxide: From waste to hydrocarbons - Cui, Lingrui; Liu, Cao; Yao, Benzhen; Edwards, Peter P.; Xiao, Tiancun; Cao, Fahai (Frontiers in Chemistry, 2022)
With rapid development of industrial society and humankind’s prosperity, the growing demands of global energy, mainly based on combustion of hydrocarbon fossil fuels, has become one of the most severe challenges all over the world. It is estimated that the fossil fuels consumption continues to grow with an annual increase rate of 1.3%, which has seriously affected natural environment by the emission of greenhouse gases, most notably carbon dioxide (CO2). Given these recognized environmental concerns, it is imperative to develop clean technologies for converting captured CO2 to high-valued chemicals, one of which is value added hydrocarbons. In this article, environmental effects due to CO2 emission are discussed and various routes for CO2 hydrogenation to hydrocarbons including light olefins, fuel oils (gasoline and jet fuel) and aromatics are comprehensively elaborated, our emphasis is on catalyst development. In addition, we present an outlook that summarizes the research challenges and opportunities associated with the hydrogenation of CO2 to hydrocarbon products.